2013
DOI: 10.1007/s11274-013-1557-0
|View full text |Cite
|
Sign up to set email alerts
|

Antidiatom activity of marine bacteria associated with sponges from San Juan Island, Washington

Abstract: Crude extracts of 52 marine bacteria associated with sponges, which were collected from the sea near San Juan Island, Washington, USA, were screened using diatom attachment assays against Amphora sp., Nitzschia closterium, Sellaphora sp. and Stauroneis sp. to investigate their antidiatom activities. Among these samples, five expressed strong anti-adhesion effects on all four tested diatoms. There was no negative effect observed from those five active samples on the growth of Amphora sp. Those five active sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Amphora was the least inhibited diatoms by Actinobacteria and marine bacteria crude extracts. This result might be appropriate with the properties of Amphora, which has two raphes on one side (ventral surface), while Navicula and Nitzschia have single raphes on ventral and dorsal side of the cell (Arce et al, 2004;Wigglesworth-cooksey and Cooksey, 2005;Jin et al, 2013). This might lead to stronger attachment for Amphora to the substrate.…”
Section: Discussionmentioning
confidence: 93%
“…Amphora was the least inhibited diatoms by Actinobacteria and marine bacteria crude extracts. This result might be appropriate with the properties of Amphora, which has two raphes on one side (ventral surface), while Navicula and Nitzschia have single raphes on ventral and dorsal side of the cell (Arce et al, 2004;Wigglesworth-cooksey and Cooksey, 2005;Jin et al, 2013). This might lead to stronger attachment for Amphora to the substrate.…”
Section: Discussionmentioning
confidence: 93%
“…Collection, isolation, and purification of the strains were performed by Coastal Marine Laboratory in Hong Kong University of Science and Technology (HKUST) as described previously [ 33 ]. One strain of UST050418-708 was selected for this study since we found that it can be active against diatom biofilm formation [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The stock solution (1 ml) was inoculated in 10 ml of the peptone-yeast extract medium (P-Y medium, containing 0.3% yeast extract and 0.5% peptone in artificial seawater (ASW)) and incubated for about two days to the exponential phase at 23°C with shaking at 120 rpm. The bacterial culture in the exponential phase was then inoculated in 500 ml of the P-Y medium and incubated for three days in the stationary phase under the same conditions and used for extract preparation [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations